Clasificación ecológica y caracterización selvícola y PRODUCTIVA DEL PARQUE NATURAL DE LOS ALCORNOCALES (CÁDIZ y MÁLAGA) - Torres Álvarez, E; Montero González, G; V ÁZQUEZ PIQUÉ, F J (II Congreso Forestal Español, 1997)
An ecological classification of the Natural Park "Los Alcornocales" (Cádiz and Málaga, Spain) and a silvicultural and productive characterisation are done. The territorial c1assification is assisted by a Geographical Information System. Sixteen Territorial Classes and five classes of cork-oak potentiality are defined and mapped. Using a sample of seventy two plots, the cork-oak forests of this area are silvicultural and productively characterised, according their Territorial Class.
Keywords: Cork; cork-oak; Ecological classification; Geographical inforn1ation system; Potentiali ty; Quercus suber

Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E Torres; González, G Montero; Suárez, M A; Cámara, D E L A; Torres Álvarez, E; Montero González, G; Suárez de la Cámara, M A (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
Keywords: cork-oak; Quercus suber; silviculture; stand density

Seguimiento de la regeneración natural de alcornoque bajo condiciones microecológicas diferentes. - Torres Álvarez, E; Montero González, G; de la cámara, m. a. (II Congreso Forestal Español, 1997)
This paper studies the natural regeneration of cork-oak in the forests of Aljibe mountains (Málaga, Spain). A plot for monitoring the development of cork-oak seedlings was installed at Cortes de la Frontera cork-oak forests, under different microecological conditions. To get a plentiful and healthy stock of seedlings is necessary enclose the area and to have a light crown cover, is the main conclusion.
Keywords: cork-oak; natural regeneration; Quercus suber; Sylviculture

Notas sobre el comportamiento de Cistus salviaefolius tras desbroces, laboreos, fertilizaciones y aplicación de fitocidas - Montoya Oliver, J M; Montero González, G (Pastos, 1977)
The Cistus salviaefolius L. is an invading and competitive species in the pastures of Quercus súber covered mounts. In order to control it we carried out some triáis of (1) rotary cutting, (2) rotary cutting -+- ploughing and (3) rotary cutting + ploughing -+- fer- tilizing, under Q. súber trees that covered 40 % aind (4) rota'ry cutting in 25 % shade: The inventory of the number of plants shows according to the comparative plots which did not undertake any treatment at all, that the reinvasion is fast and very intense. In triáis with phytocides before emergence (atrazine, simazine, bromacil and diuron) the results of control of Cistus were not as good as the ones we got in the comparative plots that were just ploughed; and besides that they produced a lack of pasture for nearly two years. The phytocides did not damage the Q. súber when using those dosis. Those results have improved the knowledge of how meteorological factors could affect the germination abi'lity of Cistus salviaefolius, that could be useful for the coming studies directed to its control. 246
Keywords: Cistus salviaefolius; desbroce; fertilización; fitocidas (voyant); laboreo